Increasing the impact of randomized controlled trials: an example of a hybrid effectiveness–implementation design in psychotherapy research. Issue 3 (26th November 2018) - Johnson, Adrienne L; Ecker, Anthony H; Fletcher, Terri L; Hundt, Natalie; Kauth, Michael R; Martin, Lindsey A; Curran, Geoffrey M; Cully, Jeffrey A
Abstract: Randomized controlled trials (RCTs) are the gold standard for clinical research. However, significant delays between completion of RCTs and adoption of evidence-based practices into clinical settings remain. Engagement of stakeholders and implementation-focused outcomes to augment traditional RCTs hold the potential to increase the impact of RCT outcomes for clinical practice and more rapidly lead to the adoption of evidence-based practices in clinical settings. The purpose of this study is to discuss hybrid effectiveness–implementation designs and use a project example to highlight important methodological considerations to enhance the impact of RCTs. A hybrid effectiveness–implementation study assessed the effectiveness and implementation potential of brief cognitive behavioral therapy (bCBT) for rural Veterans. A patient-randomized trial (bCBT vs. enhanced usual care) explored the impact on depression symptoms. Implementation elements included engagement of stakeholders and a multifaceted provider training and support program to increase bCBT use by providers in Veterans Health Administration (VA) community-based outpatient clinics. Implementation outcomes included the number of providers who adopted bCBT, provider fidelity, and delivery outcomes (e.g., use of measurement-based care, treatment engagement, and completion). Hybrid designs offer opportunities to improve the alignment between research and practice, potentially improving dissemination of evidence-based interventions and reducing known delays in the translation from research to practice. Expansion of traditional RCTs through collaborative stakeholder contributions and stakeholder/consumer-informed implementation approaches is critical to improve adoption postproject. Although hybrid designs offer significant benefits related to generalizability and adoption, these approaches involve complex procedures and processes and often come at the cost of reduced internal study controls.